American Expatriates and the Building of Alternative Social Space in Toronto, 1965–1977 - Churchill, David (Urban History Review / Revue d'histoire urbaine, 2010)
This article explores the history of U.S. expatriates and draft resisters in alternative political and cultural communities within Toronto during the late 1960s and early 1970s. As such these expatriates were important players in shaping and creating new social spaces, activist politics, and alternative forms of expression generated within the city’s counterculture communities and New Left movements. Aided by their class and racial privilege, many of these expatriates were able to participate in and engage the public culture of the city as few other migrants could. This ability to become part of the Toronto’s alternative neighbourhoods, scenes, and intentional communities was nonetheless facilitated by the transnational connections and objectives that linked local actions with global aspirations and collaborators.